Characteristics and treatment outcomes of tuberculosis cases by risk groups, Japan, 2007-2010 - Kunihiko Ito; Akira Shimouchi; Takashi Yoshiyama; Akihiro Ohkado; Lisa Kawatsu; Jintana Ngamvithayapong-Yanai; Kazuhiro Uchimura; Nobukatsu Ishikawa (World Health Organization Regional Office for the Western Pacific, 2013)
Introduction: We studied the characteristics and treatment outcomes of the following risk groups for tuberculosis (TB): those with HIV and diabetes mellitus (DM), contact cases, the homeless, foreigners, health care workers (HCW) and the elderly. Method: A descriptive cross-sectional study was conducted by analysing the Japanese TB surveillance data of all cases registered between 2007 and 2010 (N = 96 689). Results: The annual proportion of TB cases by risk group was stable over the study period, although there was a slight but significant increase observed for foreigner and elderly cases. Homeless and elderly TB cases had the highest DM co-morbidity (16.6% and 15.3%), respectively. HIV co-infection was low in all TB cases (0.2%) yet highest in foreigners (1.3%). HIV status of 45% of TB cases was unknown. The proportion of multidrug-resistant TB (MDR-TB) was similar among all risk groups (0.0%-0.9%) except foreigner, at 3.4%. Males in most risk groups had higher mortality than females; the mortality of all TB cases in all age groups for both males and females was 3.6-24 times higher than the general population. Discussion: Reasons for the high proportion of "HIV status unknown" should be investigated and improved. Contact tracing among foreign cases with MDR-TB should be a priority. Homeless persons should be screened for DM together with TB. Programmes to enhance health and nutrition status may benefit TB prevention among the elderly. Tuberculosis screening and TB education are important for HCW.